Profil Eksotropia Sensoris dan Outcomes dari Penatalaksanaan Surgikal di RSUP Dr. M. Djamil Padang Tahun 2018-2020 - Deny Wiryulisda; Julita Julita (Jurnal Health Sains, 2021)
Of the etiologies, retinal abnormalities were the most common cause of exotropia with 4 cases (33.33%). Patient management with surgical and wth monocular recess-resect surgery hangs back. From 6 months of follow-up, the patient had satisfactory cosmetic results with 85.71% orthotropia. Sensory exotropia of patients aged 21-30 years The most common cause of sensory strabismu is retinal abnormalities, and the long-term results of surgery for sensory exotropia are satisfactory. The purpose of the study was to find out the profile of sensory exotropia and outcomes of surgikal management in dr.m. djamil padang hospital in 2018-2020. The results of surgical treatment are evaluated by examining the hirsberg test and the creamy prism test. A total of 12 patients included, of whom 6 cases (50%) were men and women 6 cases (50%), and patients aged 21-30 years about 33.33%.  Evaluated for Visual acuity, through evaluation of the anterior segment using a slit lamp, and a fundus examination was performed, and found eye irregularities by conducting hisberg tests and close cream prisms and distance tests. The results of surgical treatment are evaluated by examining the hirsberg test and the creamy prism test. A total of 12 patients included, of whom 6 cases (50%) were men and women 6 cases (50%), and patients aged 21-30 years about 33.33%. Of the etiologies, retinal abnormalities were the most common cause of exotropia with 4 cases (33.33%). Patient management with surgical and wth monocular recess-resect surgery hangs back. From 6 months of follow-up, the patient had satisfactory cosmetic results with 85.71% orthotropia. Sensory exotropia of patients aged 21-30 years The most common cause of sensory strabismu is retinal abnormalities, and the long-term results of surgery forsensory exotropia are satisfactory.